LAFAZH DAN MAKNA DALAM PERSPEKTIF PEMIKIRAN LINGUISTIK IBN JINNI - Wati Susiawati (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2015)
Based on the readings and content analysis (tahlîl al-muhtawa) of Ibn Jinni’s book, al-khashâish and the other works related to linguistic thought, it was found that the notion of linguistic Ibn Jinni about the utterances and meaning are in the area of macro-linguistics that can not be separated from the study of phonology, morphology , syntax, and semantic. In addition, it cannot be separated from one another, utterances and meaning in Arabic, according to Ibn Jinni, it is used and developed as a medium of communication, both spoken and written. Therefore, word and meaning must be understood in the process, the events and the context of linguistic and socio-cultural context as a whole. Word and meaning of the object of study is the linguistic multiperspective, thus giving birth to the various fields of linguistic science. Linguistic thought about the word and meaning is important not only serve as a theoretical basis for understanding the text in Arabic, but also significantly to the development of learning 'ilm al-dalâlah (semantics) to the Arabic leaner or scholar.DOI: 10.15408/a.v2i2.2133